2022
DOI: 10.1007/s41748-022-00308-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil Erosion Vulnerability Mapping in Selected Rural Communities of uThukela Catchment, South Africa, Using the Analytic Hierarchy Process

Abstract: Soil erosion remains one of the main causes of land degradation, affecting many countries across the globe including South Africa. In rural communities with much reliance on agriculture, soil erosion is an important threat to food security. Therefore, mapping erosion-prone areas is an essential step towards adopting appropriate erosion mitigation and soil conservation measures. The objectives of this study were to (i) assess and model soil erosion vulnerability based on the Analytic Hierarchy Process (AHP) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The dominance of extreme precipitation in Free State, KwaZulu-Natal, Mpumalanga, and partly Eastern Cape provinces demonstrated that these regions were prone to flooding and water erosion. As reported by Ebhuoma et al 88 , it was estimated that 35% of the upper uThukela catchment in KwaZulu-Natal was at risk to soil degradation caused by water. Besides the degree of slope and vegetation cover, the precipitation in KwaZulu-Natal influenced soil erosion with a weight factor of 18%.…”
Section: Discussionmentioning
confidence: 82%
“…The dominance of extreme precipitation in Free State, KwaZulu-Natal, Mpumalanga, and partly Eastern Cape provinces demonstrated that these regions were prone to flooding and water erosion. As reported by Ebhuoma et al 88 , it was estimated that 35% of the upper uThukela catchment in KwaZulu-Natal was at risk to soil degradation caused by water. Besides the degree of slope and vegetation cover, the precipitation in KwaZulu-Natal influenced soil erosion with a weight factor of 18%.…”
Section: Discussionmentioning
confidence: 82%
“…The AHP is a suitable technique for identifying and mapping erosion-prone areas (Belkendil, A. et al 2018;Belloula, M. et al 2020;Aslam, B. et al 2021;Sinshaw, B.G. et al 2021;Ebhuoma, O. et al 2022). AHP is a method that compares qualitative factors and expresses them as numerical values.…”
Section: Analytic Hierarchy Processmentioning
confidence: 99%
“…where Sl is the slope, As is the aspect, Li is the lithology, El is the elevation, Pr is the precipitation, Drd is the drainage density, and W were reclassified into six categories: insignificant, very low, low, moderate, high, and very high (Ebhuoma, O. et al 2022). It is noteworthy that, owing to the seasonal variation in the impact of each factor, the erosion susceptibility maps encompass different categories.…”
Section: The Winter Seasonmentioning
confidence: 99%